2016
DOI: 10.1001/jamasurg.2016.1670
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mentorship Programs in Departments of Surgery in the United States

Abstract: These data show that only half of departments of surgery in the United States have established mentorship programs, and most are informal, unstructured, and do not involve all of the key stakeholders. Given the importance of mentorship to career satisfaction and retention, development of formal mentorship programs should be considered for all academic departments of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 23 publications
2
82
3
1
Order By: Relevance
“…All respondents reported either formal (43.6%) or informal (56.4%) faculty mentoring programs. This differs from a recent survey of mentoring practices in departments of surgery in which only 54% of chairs reported having established mentoring programs ( n = 41/76), most of which were informal and unstructured …”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…All respondents reported either formal (43.6%) or informal (56.4%) faculty mentoring programs. This differs from a recent survey of mentoring practices in departments of surgery in which only 54% of chairs reported having established mentoring programs ( n = 41/76), most of which were informal and unstructured …”
Section: Discussioncontrasting
confidence: 93%
“…This implies that although mentoring is an expectation, many basic structures to support and cultivate mentorship may not be in place. These findings are similar to those of other studies on faculty mentoring, including those from EM, that have identified similar gaps in mentoring training, establishing expectations, and the evaluation process . This opens up opportunities for EM to learn from more robust programs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Low-quality mentorship is not only observed in CM&ID training but also broadly recognised among other medical specialties as well as in academic medicine [57, 12, 13, 1517]. Barriers to mentoring and inadequate mentoring can be related to many factors including personal, relational, and structural barriers [12].…”
Section: Discussionmentioning
confidence: 99%
“…Participation in these formal mentoring programs has been shown to improve academic and research productivity and work satisfaction among junior clinical and translational research faculty [1]. While mentorship programs exist throughout departments of surgery and surgical societies across the country, many are unstructured with no clear evidence of routine evaluation or formal analysis of outcomes [2]. …”
Section: Introductionmentioning
confidence: 99%